Developing Hanyut Lancang Local Wisdom-Based Interactive Multimedia to Enhance Student Tolerance - Araida Purba; Reh Bungana Beru Perangin-angin; Hapni Laila Siregar; Surya Dharma; Yakobus Ndona; Yusnadi (Researchparks Publishing, 2026)
This study aims to develop viable, practical, and effective interactive learning multimedia based on Hanyut Lancang local wisdom to enhance the tolerance character of fifth-grade students at SD Negeri 132410 Tanjungbalai. Utilizing the 4-D Research and Development (R&D) model comprising Define, Design, Develop, and Disseminate the study yielded several key findings. First, media feasibility validation by material, media, and language experts achieved